Comparism between Anti-RA33, Anti-CCP antibodies and Rheumatoid Factor in the Diagnosis of Rheumatoid Arthritis in Iraqi Patients - Al-Ubaidi, Ammar H.; Marrof Al-Ani, Mohammed; Al-Bidri, Khudhayer Z. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Anti-RA33 antibodies and anti-CCP antibodies are highly specific markers for rheumatoid arthritis (RA), but are not detectable in all RA patients.Anti-RA33 antibodies are directed to the heterogeneous nuclear ribonucleoprotein A2 (hnRNP-A2),while anti-CCP antibodies are directed to modified epitope on proteins that undergo conversion of amino acid arginine to citrullin by citrullination.Objectives: The aim of this study was to show the correlation between anti-RA33 antibodies, anti-CCP antibodies and rheumatoid factor (RF) in terms of sensitivity and specificity for the diagnosis of rheumatoid arthritis in Iraqi patients.Subjects and methods: This study was conducted in the period between December 2010 and April 2011 on 70 subjects. Forty five (45) of them were diagnosed as established RA patients and they were on treatment (the patients group) who were attending the rheumatology out patients clinic or admitted to Baghdad teaching hospital ,and twenty five (25) subjects were healthy(the control group). From each subject 5mls of venous blood was aspirated and centrifuged to separate the serum. The sera were stored at -20C and tested for anti-RA33 antibodies, anti-CCP antibodies, and RF (IgM) antibodies using enzyme linked Immunosorbent assay (ELISA) kit.Statistical analysis in this study was done according to spss version 7.Results: There were thirty eight (38) seropositive (RF positive) patients (84.4%) and seven (7) seronegative (RF negative) patients (15.6%),with thirty(30) (66.6%) patients were anti-CCP antibodies positive and fifteen (15) (33.4%) patients anti-CCP antibodies negative, while there were twenty five(25)(55.6%) patients anti-RA33 antibodies positive and (20)(44.4%) patients were anti-RA33 antibodies negative.Conclusion: Anti-CCP antibodies have the highest specificity and rheumatoid factor has the highest sensitivity than anti-RA33 antibodies, but anti-RA33 antibodies are helpful in patients who are anti-CCP negative and RF negative.